APPLYING WEBBING STRATEGY IN TEACHING READING COMPREHENSION - Fatha, Asriful; R. Mertosono, Sudarkam; Jamiluddin, Jamiluddin (e-Journal of ELTS (English Language Teaching Society), 2023)
The research aims to determine whether Applying Webbing Strategy can improve students’ reading comprehension grade Eight students of SMPN 1 Sojol. This research applied a quasi-experimental research design. The research sample was Eight D as the experimental group, which consisted of 25 students, and Eight A as the control group, which consisted of 27 students. The instrument used in collecting the data were pre-test and post-test. The treatment was given six times. The data were analyzed statistically to determine the difference between the pre-test and post-test. As a result of the study, the mean score of the experimental group taught by applying webbing strategy was improved compared to the control group taught without applying webbing strategy. In other words, applying webbing strategy can improve the reading comprehension of grade eight students of SMPN 1 Sojol.